(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Mediation, a type of Alternative dispute mechanism plays an important role in resolving the dispute by acting as a neutral party and enforcing the principles to be followed as outlined. The act gives the right to the parties to appoint, terminate and replace the mediators for the lawsuit as per the mentioned time. Furthermore, the availability of online mediation is advantageous and prominent in the digital era for dispute resolution mechanisms, the time-bound process makes mediation more suitable for legal practitioners for commercial, civil and institutional disputes. The purpose of establishing the Mediation Council of India under the act is to promote professionalism and ensure a high success rate in dispute resolution. The Mediation act is a cost-effective resolution method and flexible to meet the requirement and maintain a high level of confidentiality to protect the interests of the parties. This study envisages the use of mediation to resolve the legal dispute in a hassle-free and solution-oriented manner. The recent enactment of the Mediation Act 2023 has achieved substantial advances in dispute management by being the most effective and robust method of resolving disputes among the parties. This statute has been more advantageous and supportiveof settling legal fights in a calm and process-oriented manner than the adversarial justice system, which is unable to provide justice due to an overburdened backlog of lawsuits. Moreover, the preamble of the Act, emphasises community mediation to make the dispute resolution to the mass. This paper provides an depth guide on the Mediation Act and its features, advantages and challenges under alternative dispute resolution.